Individual thermoelectric properties of electrodeposited bismuth telluride nanowires in polycarbonate membranes. (10th April 2015) - Chang, Taehoo; Cho, Sungmee; Kim, Jeongmin; Schoenleber, Jonathan; Frantz, Cedric; Stein, Nicolas; Boulanger, Clotilde; Lee, Wooyoung
ABSTRACT: In this study, we examined individual bismuth telluride nanowires (NWs) electrodeposited in polycarbonate membranes (PCM) used as sacrificial templates. It has been demonstrated that the composition of Bi2 Te3 is controlled by the electrodeposition conditions, e.g. the applied potential. High-resolution transmission electron microscopy (HRTEM) shows that the average grain size of NWs increases with increasing Te content. Our results also reveal that the electrodeposited bismuth telluride NWs are n -type, and their electrical conductivity increases with increasing Te content. These NWs also demonstrated a maximum power factor of 195.8 mW/m·K 2 for the Te-rich NW (d = 162 nm) at 300 K.